The quality of registration of clinical trials: still a problem. - Roderik F Viergever (Public Library of Science (PLoS), 2014)
Introduction The benefits of clinical trials registration include improved transparency on clinical trials for healthcare workers and patients, increased accountability of trialists, the potential to address publication bias and selective reporting, and possibilities for research collaboration and prioritization. However, poor quality of information in registered records of trials has been found to undermine these benefits in the past. Trialists' increasing experience with trial registration and recent developments in registration systems may have positively affected data quality. This study was conducted to investigate whether the quality of registration has improved. Methods We repeated a study from 2009, using the same methods and the same research team. A random sample of 400 records of clinical trials that were registered between 01/01/2012 and 01/01/2013 was taken from the International Clinical Trials Registry Platform (ICTRP) and assessed for the quality of information on 1) contact details, 2) interventions and 3) primary outcomes. Results were compared to the equivalent assessments from our previous study. Results There was a small and not statistically significant increase from 81.0% to 85.5% in the percentage of records that provided a name of a contact person. There was a significant increase from 68.7% to 74.9% in the number of records that provided either an email address or a telephone number. There was a significant increase from 44.2% to 51.9% in the number of intervention arms that were complete in registering intervention specifics. There was a significant increase from 38.2% to 57.6% in the number of primary outcomes that were specific measures with a meaningful timeframe. Approximately half of all trials continued to be retrospectively registered. Discussion There have been small but significant improvements in the quality of registration since 2009. Important problems with quality remain and continue to constitute an impediment to the meaningful utilization of registered trial information.